Exploring language assessment literacy: Indonesian pre-service English teachers’ perceived readiness for classroom assessment - Nanin Verina Widya Putri; Anisa Fitri; Edi Suwandi; Bendaoud Nadif; Riza Nur Diana; Marwah Qurrota A’yun (Universitas Islam Malang, 2026)
Understanding language assessment literacy (LAL) is an important part of pre-service English teachers’ professional development. Although interest in language assessment has increased, studies focusing on pre-service teachers’ LAL in the Indonesian EFL context remain limited. A clearer understanding of how pre-service teachers view and interpret classroom assessment is therefore needed to support more effective assessment practices and improve language teaching and learning. This qualitative study explores Indonesian EFL pre-service teachers' perceived readiness for classroom assessment by examining how aspects of LAL are articulated through interview data. The study involved ten English education study program students who had completed the teaching practicum program in East Java, Indonesia. The findings indicate that, despite expressing confidence in their readiness to teach, the participants demonstrated limited and uneven understandings of key LAL components. The small number of participants and the specific institutional context limit the transferability of the findings. Nevertheless, this study suggests that closer attention to LAL within pre-service English teachers’ education may help support the development of more balanced assessments.